RENCANA MODEL BISNIS DISTRO BALITA DISTA - , Larasayu Imas Indarini, Risa Virgosita, SE., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Distro or distribution store is a place and a clothing distributor that manufactures and sells its own products in limited quantities and also market their products through other distributors and other distributions or receive product called consignment. Distributions in Yogyakarta has only among teenage target markets because teenage usually like to be different either individually or groups in the selection of fashion and in Yogyakarta still rare distro target market for toddlers. Growth of toddlers in Indonesia including fast that the need for toddler clothes daily will also increase. The unit analysis of this research is an attempt at DIY Dista Distro. This research analyzed the distribution business and baby clothing store that has been in Yogyakarta. Research on the distribution and baby clothing store that has been conducted to determine the distribution business model in general. Tool in this research using customer empathy map and business model canvas. Empathy map is a tool to get a deeper knowledge of the consumer based on what consumers see, hear, think and feel, say and do, pain or anything that does not want to be perceived, and what you want to get the consumer to develop new value propositions. Analysis of the business model canvas Dista Distro using nine main elements, customer segments, value propositions, channels, customer relationship, key activities, key resources, key partners, revenue streams, and cost structure. Dista distro offers a business model such as limited product design and not the same as in the market, a guarantee in the form of exchange of goods that do not comply, the facility where children play, the creation parcel services to send gifts, and also online media services have to know the products recent and enable customers to make purchases of products Dista Distro.